Treadmill training combined with transcranial direct current stimulation over the primary motor cortex in a child with cerebral palsy and hydrocephalus: A case report. - Rezende, Fernanda Lobo; Duarte, Natália de Almeida Carvalho; Grecco, Luanda André Collange; Oliveira, Claudia Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Transcranial direct current stimulation (tDCS) is a promising technique that stimulates the cortex with a direct, low-intensity electric current and can potentiate motor learning. Objective: Describe the results of an intervention protocol involving anodal stimulation over the primary motor cortex combined with treadmill training in a child with cerebral palsy. Method: The intervention was comprised of ten sessions of anodal tDCS (1mA) over the primary motor cortex during the treadmill training. Stabilometric analysis was evaluated one week before and one week after the intervention. Results: A reduction in oscillations of the COP was found under both conditions (eyes opened and eyes closed. Conclusion: Our findings suggest that anodal tDCS over primary motor cortex can potentiate the results of treadmill training.